Circular approach of greener broiler chicken production - Kiss, Nikolett Éva; Nagy, Attila; Tamás, János (Frontiers in Built Environment, 2025)
The sustainability of agricultural production is a key issue, particularly in terms of fertilizer use, greenhouse gas emissions, and resource depletion. This study uses life cycle assessment (LCA) to compare the environmental impacts of composted and pelletized poultry manure (CPPL) and six different fertilizers (ammonium nitrate (AN), calcium ammonium nitrate (CAN), urea, monoammonium phosphate (MAP), triple superphosphate (TSP), and potassium chloride (KCl)) during corn and winter wheat production, as well as their impact on broiler chicken production. The study also took into account different fertilization methods and seasonal variations (summer and winter rotation), analyzing eleven environmental impact categories, including global warming potential (GWP), acidification potential (AP), eutrophication potential (EP), abiotic resource use (abiotic depletion potential for elements (ADPe), abiotic depletion potential for fossil fuels (ADPf)), ozone layer depletion potential (ODP), photochemical oxidation potential (POP) and ecotoxicity potentials (freshwater aquatic ecotoxicity potential (FAETP), human toxicity potential (HTP), marine aquatic ecotoxicity potential (MAETP), terrestrial ecotoxicity potential (TETP)). Based on the results, GWP was 11%–14% lower for CPPL production compared to fertilizers, while ADPf was 14%–56% lower. At the same time, AP was significantly higher for CPPL, mainly due to ammonia emissions. In crop production (corn, winter wheat), CPPL-based nutrient replenishment resulted in 11%–34% lower GWP and 14%–56% lower ADPf in most environmental scenarios compared to fertilizer treatments. In toxic impact categories (e.g., FAETP, MAETP), reductions of 3%–15% were observed. However, AP values were 2.6%–6.8% higher, and EP could be up to twice as high as for fertilizer treatments. In broiler chicken farming, when feed was produced from CPPL-grown crops, the environmental impact was 30%–85% lower in almost all categories examined than with fertilizer-based feed. Seasonal differences were moderate, with a 3%–5% increase in some categories during winter. Based on the results, CPPL offers a promising alternative to chemical fertilizers, especially in reducing greenhouse gas emissions and nutrient leaching. In line with circular economy principles, CPPL can contribute to the development of more sustainable agricultural systems.